Regulation of the non-selective Na+ importer capacity of NRT1.2/NPF4.6/AIT1 by SOS2-mediated phosphorylation in Arabidopsis - Xiaoxiao Liu; Lei Zhang; Zeqi Zhao; Yue Zheng; Yue Ren; Xiaomin Zhao; Shizhong Zhang; Guodong Yang; Jinguang Huang; Kang Yan; Chunlong Li; Chengchao Zheng; et al. (Cell Reports)
Summary: Although preventing sodium ion import is crucial for salt tolerance, the mechanisms and the Na+ importers involved remain unclear. We identified NRT1.2/NPF4.6/AIT1 as a non-selective Na+ importer. NRT1.2 overexpression in Arabidopsis increased salt sensitivity due to Na+ accumulation, while nrt1.2 mutants exhibited opposite results. Non-invasive micro-test technology indicated Na+ uptake capability of NRT1.2 in Arabidopsis roots. When expressed in Xenopus laevis oocytes, NRT1.2 displayed low-pH-dependent and NO3−-promoted Na+, K+, and Li+ importer capacity, conferring higher potassium and lithium tolerance in NRT1.2 overexpression plants. Mechanically, salt overly sensitive 2 (SOS2) phosphorylated NRT1.2 at Thr248, reducing its Na+ import and preventing excessive Na+ accumulation. Prolonged salt stress also downregulated NRT1.2 transcripts. In summary, our findings unveil a role of NRT1.2 in Na+ transport and a regulatory pathway via SOS2-mediated phosphorylation of NRT1.2 at Thr248, crucial for plant salt-stress adaptation.